Respiratory hazards in hard metal workers: a cross sectional study. Issue 5 (May 1989) - Meyer-Bisch, C; Pham, Q T; Mur, J M; Massin, N; Moulin, J J; Teculescu, D; Carton, B; Pierre, F; Baruthio, F
Abstract : A cross sectional study was conducted on 513 employees at three hard metal plants: 425 exposed workers (351 men, 74 women) and 88 controls (69 men, 19 women). Cough and sputum were more frequent in workers engaged in "soft powder" and presintering workshops compared with controls (12.5% and 16.5% v 3.5%). Spirometric abnormalities were more frequent among women in sintering and finishing workshops compared with control women (56.8% v 23.8%) and abnormalities of carbon monoxide test were more frequent in exposed groups than in controls; this difference was more pronounced in women (31.4% v 5.6%) than in men (18.5% v 13%). No significant correlation was observed between duration of exposure and age adjusted lung function tests. Slight abnormalities of chest radiographs (0/1, 1/1 according to ILO classification) were more frequent in exposed men than controls (12.8% v 1.9%) and mostly in soft powder workers. In subjects with abnormal chest radiographs FVC, FEV1 and carbon monoxide indices (fractional uptake of CO or CO transfer index or both) were lower compared with those with normal chest radiographs. Although relatively mild, the clinical, radiological, and functional abnormalities uncovered call for a regular supervision of workers exposed to hard metal dust.